Revisiting Islamic Philosophy: Ethical Insights for Education, Social Equity, and Technological Responsibility - Tirta, Tirta Alim Wiliam Diaz (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study investigates the contribution of Islamic philosophy to shaping an ethical society, focusing on its relevance in education, social development, and addressing the challenges posed by technology and globalization. The central question explored is how Islamic philosophical principles can serve as a foundational framework for ethical values in contemporary contexts. Employing a qualitative approach through a literature study, this research analyzes the works of classical Islamic philosophers and examines their applicability to modern societal issues. The findings highlight that Islamic philosophy emphasizes the centrality of education rooted in moral and social values, fostering inclusive and equitable social development. It also offers critical ethical guidance on the responsible use of technology and the socio-cultural impacts of globalization. By bridging classical thought with modern challenges, this study underscores the enduring relevance of Islamic philosophical principles in providing holistic and value-driven solutions to contemporary problems. The originality of this research lies in its application of Islamic ethical values to modern dilemmas, demonstrating their potential to address pressing issues in education, social cohesion, and technological advancement. This work contributes to ongoing scholarly discussions on the role of religion and philosophy in creating a just and ethical global society.